INFORMALIDADE URBANA: REPRESENTAÇÕES SOCIAIS DA MÍDIA SOBRE A INFORMALIDADE HABITACIONAL URBANA NA CIDADE DA PRAIA - Rutte Tavares Cardoso Andrade (European Scientific Journal, ESJ, 2014)
Cape Verde met a considerable development, taking into consideration the 36thyear as an independent country. Nevertheless, this development is also marked by contradictions, mainly regarding the social dimension of the guarantee of social sector living conditions, which is still very vulnerable, since it faces issues of informality. Based on this idea, this research seeks to address the process of development of the peripheries of the country, especially the peripheries of Praia. This work seeks to answer how they are configured and what symbolic meanings around them are created by the media. The results show that the media makes a negative representation of informal urban housing in the city of Praia. In addition it stigmatizes and promotes social exclusion of the social segments that live in informal housing.